Աւանդութիւններ եւ պատմական յիշատակութիւններ Հայոց միւռոնի մասին - Ազիզեան, Արամայիս սրկ. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Изучая исторические источники, мы попытались представить предания о происхождении мюрона (мира) в армянской среде, а также библиографические справки о его благословении и употреблении (IV—XVIII вв.). Согласно историческим источникам, в Армянском мюроне содержится часть освященного пророком Моисеем елея для помазания, что придает ему большую силу. В библиографических упоминаниях в основном говорится о чудодейственной силе Армянского мюрона, но случалось также, что было неуважительное отношение к мюрону, в частности у тондракийцев и павликиан. By studying the historical sources, we have tried to present the traditions about the origin of the Holy Myron in the Armenian reality, as well as the bibliographic references regarding the use and blessing ceremonies of the Holy Myron (4th—18th centuries). According to historical sources, the Armenian Holy Myron contains a part of the anointing oil blessed by Prophet Moses, which gives it greater power. The bibliographic references about the Holy Myron mainly talk about the miraculous power of the Armenian Holy Myron, but there were also cases of a contemptuous attitude towards it, in particular, by the Tondrakians and Paulicians.
Keywords: Կրօնագիտութիւն